2008
DOI: 10.1017/s0033291708004881
|View full text |Cite
|
Sign up to set email alerts
|

A study of psychiatrists' concepts of mental illness

Abstract: BackgroundThere are multiple models of mental illness that inform professional and lay understanding. Few studies have formally investigated psychiatrists' attitudes. We aimed to measure how a group of trainee psychiatrists understand familiar mental illnesses in terms of propositions drawn from different models.MethodWe used a questionnaire study of a sample of trainees from South London and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 15 publications
1
58
1
Order By: Relevance
“…As outlined in the literature review, clinicians' views and assumptions about mental health have been found to guide and inform their approaches to assessment, formulation, and intervention (Harland et al, 2009) and to shape service users' views about their conditions (Ahn et al, 2009). This implies that there is a need for clinicians to be honest about the contingent and situated nature of their knowledge and language, to make their assumptions about mental health explicit, and to be mindful of the effects of their use of language on different stakeholders in talking about mental health.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in the literature review, clinicians' views and assumptions about mental health have been found to guide and inform their approaches to assessment, formulation, and intervention (Harland et al, 2009) and to shape service users' views about their conditions (Ahn et al, 2009). This implies that there is a need for clinicians to be honest about the contingent and situated nature of their knowledge and language, to make their assumptions about mental health explicit, and to be mindful of the effects of their use of language on different stakeholders in talking about mental health.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lay population may interpret a DSM-defined mental disorder as God's will (Link et al, 1999;Wesselmann & Graziano, 2010), a sign of weakness Schnittker, Freese & Powell, 2000), or a result of upbringing (Kuppin & Carpiano, 2006). Many lay definitions tend to be broader, and exclude many symptoms used in the diagnostic manual (Granello & Granello, 2000;Harland et al, 2009;Pescosolido et al, 2000;Link, Phelan, Beshnahan, Stueve, & Pescosolido, 1999;Kuppin & Carpiano;. Given a lack of agreement among mental health professionals and between professionals and lay people regarding what is and what causes mental illness, there continues to be a discrepancy in understanding what constitutes a mental illness in American society.…”
Section: Conceptions Of Mental Illness In the United Statesmentioning
confidence: 99%
“…Today a strongly endorsed approach in psychiatry is the socalled medical or disease model of mental disorder (Harland et al 2008). The medical model is a view of mental disorder according to which a mental disorder is a medical disease (Murphy 2006;Andreasen 1984Andreasen , 2001Kandel 1998).…”
Section: The Medical Model Of Mental Disordermentioning
confidence: 99%
“…For example, a genetic predisposition for depression may express itself only if triggered by a major stressful life event (Kendler et al 2003). If we take the case of schizophrenia, the disorder for which the medical model is most strongly endorsed (Harland et al 2008), there is no evidence for one common underlying biological correlate of psychosis, either genetic or neurophysiological (Kidd 1997;Flashman and Green 2004). Rather, psychosocial/ environmental factors like living in an urban area, living with families with high expressed emotion, drug use during adolescence or belonging to a minority group are contributing causes of a large number of schizophrenia onset incidents and their post-onset course (Kavanagh 1992;Sundquist et al 2004;Broome et al 2005;Van Os et al 2008;van Os et al 2010;Pharoah et al 2010).…”
Section: Why Integrative Explanatory Pluralism?mentioning
confidence: 99%
See 1 more Smart Citation